As estratégias de leitura sem e com o uso do Google tradutor - Karnal, Adriana Riess (2015)
This dissertation investigates reading strategies in Reading comprehension in academic texts in English as a L2 /FL when translated or not by Google translator. The study is based on the psycolinguistics perspective of reading, focusing on the research in foreing languages (CARRELL, 1988; GRABE, 2009; KODA, 2005). From this perspective, reading strategies are discussed as well as lower abilities such as lexical knowledge or parsing and higher abilities such as inferences. Moreover, reading models are analyzed and the interactive models (those who deal with bottom up and top down processing) are central to the dissertation.Perfetti´s model called Lexical Quality Hypothesis (2001, 2007) is also discussed. Another issue that underpins this investigation is the evolution of Computational Linguistics, specifically the area of Machine Translation. We analyse Google translator and how it can also be used as a reading strategy in English as a L2 to comprehend academic texts. In addition, this dissertation explores how the electronic translator can be utilized to teaching\learning of reading in English as a L2. In order to evaluate if this digital tool is a benefit to reading comprehension ten intermediate students from various nationalities from the English language institute of the University of Pittsburgh participated in the research. The methodology of Verbal protocols was conducted where subjects could either use Google or not. Qualitative analyses was carried out and it was observed how reading strategies were used so that we could compare them when the translator was used. Data analyses show that more strategies are used when participants read with Google and they are able to articulate their knowledge more adequately. It was also verified that lexical access Google translator promotes is beneficial to reading. Yet, the use of Google suggests that there is an approximation of linguistic knowledge between readers at different levels of proficiency. This means that the translator approximates the ones who know more from those who are less proficient.